Relationship between Presenting and Final Visual Acuity in Penetrating Corneal Injury Patients in a Tertiary Eye Hospital of Bangladesh - Naim, Tajkiratun; Quader, Md Abdul; Sarkar, Shayamal Kumar; Rahman, Md Aminur; Afroze, Farzana; Yousuf, Fawaz Bin; Haque, Mahabubul (Journal of National Institute of Ophthalmology, 2025)
Background: Penetrating corneal injury is a full thickness penetration of the cornea. Early management can regain useful final visual acuity and can prevent blindness by reducing complications. Objective: To evaluate the relationship between presenting & final visual acuity in penetrating corneal injury patients. Methods: This prospective observational study was aimed to evaluate the relationship between the presenting and final visual acuity (VA) of penetrating corneal injury patients, where 104 eyes were studied in National Institute of Ophthalmology & Hospital (NIO&H) from the year 2021 to 2023. Detailed ophthalmic examinations of the patients were done including the presenting visual acuity, anterior and posterior segment. Follow up was done after 7 days, after 1 month, 3 months and 6 months with best corrected final VA at 6th month. Results: This study showed the median (IQR) age for the subjects was 27.0 (20.0-40.0) years. There were 89 males (85.6%) and 15 females (14.4%). Majority of the patients (57.7%) came within 24 hours of injury. Majority of the patients (61.5%) presented with mono ocular blindness (VA<3/60), where 1% presented with normal or mild visual impairment. Majority were caused by sharp objects (61.5%) followed by wooden stick (15.4%), road traffic injury (10.6%) and metallic objects (7.7%). Finally, 58.9% patients regained Final VA 6/6-6/18 and 11.6% were blind. In the 6 months follow up period, 22.1% patients had complications which included traumatic cataract, vitreous hemorrhage, endophthalmitis, retinal detachment and phthisis bulbi. Factors affecting poor final VA were poor initial VA (p=<0.001), older age (p=0.005), delayed presentation (p=0.016), central corneal injury (p=0.008), larger size of injury (p=0.001), and presence of complications (p=<0.001). Conclusion: Better initial visual acuity results in a favorable final VA. Central corneal injury, older age, large sized injury, delayed presentation and presence of complication cause poor final VA. J.Natl.Inst.Ophthalmol. 2023; 6(2):38-45